1999
DOI: 10.1021/ic990328x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Configuration of Ferric Ions in Low-Spin (Dicyano)(meso-tetraarylporphyrinato)iron(III) Complexes

Abstract: The electron configuration of a series of low-spin (dicyano){meso-tetrakis(2,4,6-trialkylphenyl)porphyrinato}iron(III) complexes, [Fe(R-TPP)(CN)2]- where R = Me, Et, or iPr, together with the parent [Fe(TPP)(CN)2]-, has been examined in dichloromethane−methanol solution by 1H NMR, 13C NMR, and EPR spectroscopies. While the ferric ion of [Fe(TPP)(CN)2]- has shown a common (d xy )2(d xz ,d yz )3 configuration, the ferric ions of the alkyl-substituted complexes [Fe(R-TPP)(CN)2]- have exhibited the preference of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 54 publications
6
45
0
2
Order By: Relevance
“…Spectral and analytical data have been already extensively reported in the literature. [9] Compound 1. The synthesis of this compound was previously reported elsewhere in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Spectral and analytical data have been already extensively reported in the literature. [9] Compound 1. The synthesis of this compound was previously reported elsewhere in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…142 De qualquer maneira, a atribuição tanto do estado de coordenação como da natureza do ligante coordenado no sexto sítio de coordenação é um pré-requisito para tais estudos. 142 Em hemoproteínas, distorções assimétricas do macrociclo porfirínico são induzidas por ligantes axiais, [143][144][145] O fato da porfirina desenvolver diversas funções em biologia é uma clara evidência da influência do ambiente proteico sobre suas propriedades. 153 Segundo Marques e Brown, 153 um dos mais significativos desenvolvimentos na química das porfirinas nos últimos 20 anos consiste nos estudos focados na flexibilidade do anel porfirínico.…”
Section: A Configuração Eletrônica Dos Grupos Heme Férricos Para Os Sunclassified
“…The assignment was then completed with the [a] OEP: octaethylporphyrin in CD 3 OD. [8] [b] TPP: tetraphenylporphyrin in CD 2 Cl 2 /CD 3 OD at 202 K. [21] [c] At 298 K. [23] [d] At 308 K.…”
Section: Low-spin Complexesmentioning
confidence: 99%
“…The former studies generally indicated that the electronic ground state was (d xy ) 2 (d xz ,d yz ) 3 for these complexes. However, more recently, it was shown that the bis(cyanido) complexes of meso-substituted Fe III porphyrins having alkyl substituents of increasing size [17] and other iron(III) porphyrins having bulky substituents in the meso position [18][19][20][21] show a large shift in the pyrrole protons towards the diamagnetic region, which is indicative of a large contribution of the unusual (d xz d yz ) 4 2 ] appear at very high magnetic field (δ = -10 to -20 ppm). This large upfield shift of the β-pyrrole protons indicates the existence of large spin densities on the β-pyrrole carbons, which is induced by the interactions between porphyrin 3e g and iron d π orbitals.…”
Section: Electronic Ground State Of Low-spin Complexesmentioning
confidence: 99%